2012
DOI: 10.1590/s1519-69842012000500007
|View full text |Cite
|
Sign up to set email alerts
|

Use of ecological niche models to predict the distribution of invasive species: a scientometric analysis

Abstract: We conducted a scientometric analysis to determine the main trends and gaps of studies on the use of ecological niche models (ENMs) to predict the distribution of invasive species. We used the database of the Thomson Institute for Scientific Information (ISI). We found 190 papers published between 1991 and 2010 in 82 journals. The number of papers was low in the 1990s, but began to increase after 2003. One-third of the papers were published by researchers from the United States of America, and consequently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
1
25
1
2
Order By: Relevance
“…Assessments of the state of development of a certain area may help to improve and develop new postulates, concepts and paradigms. Our results showed that over 21 years, the number of publications on Chl-a has continued to grow, a pattern also found in other scientometric studies, for instance on phytoplankton (CARNEIRO et al, 2008), macrophytes (PADIAL et al, 2008), population ecology (LIMA-RIBEIRO et al, 2007), genetic studies using flow cytometry (QUIXABEIRA et al, 2010), niche models used in invasive species (BARBOSA et al, 2012) and global climate change (NABOUT et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Assessments of the state of development of a certain area may help to improve and develop new postulates, concepts and paradigms. Our results showed that over 21 years, the number of publications on Chl-a has continued to grow, a pattern also found in other scientometric studies, for instance on phytoplankton (CARNEIRO et al, 2008), macrophytes (PADIAL et al, 2008), population ecology (LIMA-RIBEIRO et al, 2007), genetic studies using flow cytometry (QUIXABEIRA et al, 2010), niche models used in invasive species (BARBOSA et al, 2012) and global climate change (NABOUT et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…However, majority of studies were carried out in terrestrial environments and only a few investigated aquatic systems (Barbosa, Schneck, & Melo, 2012). Probably limitation of SDM for freshwater taxa is related to lack of sufficiently ecological data layers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A regression tree (De'Ath and Fabricius 2000) was used to identify possible trends over time for the number of papers on L. fortunei (see Barbosa et al 2012 for a similar use of this method). The number of papers on L. fortunei was standardized over time by dividing it by the total number of papers in the ISI database in a given year, and multiplying the result by 10,000.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 51 papers were cited more than five times, which does not support the pattern suggested by Garfield (2006), in which most published papers are never cited or cited only a few times. Similarly, in a recent scientometric study, Barbosa et al (2012) showed that 60% of the papers on the use of ecological niche models to predict the distribution of invasive species were cited more than five times. Among the most-cited papers, that by Ricciardi (1998), which is a review of the biology and invasion history of L. fortunei in Asia (Hong Kong, Japan, and Taiwan) and South America (Argentina and Uruguay), evaluates its potential range of expansion into North America.…”
mentioning
confidence: 93%